Analisis Yuridis Pengajuan Permohonan Penundaan Kewajiban Pembayaran Utang terhadap Perusahaan Efek Ditinjau dari Asas Kemanfaatan (Studi kasus Putusan Nomor: (78/PDT.SUS-PKPU/2020/PN.Niaga.Jkt.Pst) - Yusrizal Yusrizal (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine how the regulation related to PKPU against Securities Companies and how the position of customers in applying for PKPU against securities companies in decision Number: 78/PDT.SUS-PKPU /2020 /PN.Niaga.Jkt.Pst as well as legal benefits for the community. This type of research is normative juridical. The results of this study indicate that the PKPU regulation against securities companies is regulated in Law No. 37 of 2004, Law No. 21 of 2011 concerning the Financial Services Authority, Law No. 8 of 1995 concerning the Capital Market and the judge's consideration in granting the application submitted by the creditor against the securities company to the Commercial Court was incorrect because the customer did not have legal standing because based on Article 223 Jo Article 2 paragraph (5) jo. Article 55 that only OJK can apply for PKPU against securities companies. The judge's consideration is not in line with the purpose of law, namely legal certainty, but the judge's consideration has the goal of achieving legal benefits for customers or justice-seeking communities.